Pengemasan Materi Ajar Tari Gobuk melalui Aplikasi Youtube untuk Siswa Sekolah Menengah Atas - Putri, Didra Amira; Heniwaty, Yusnizar (Gesture: Jurnal Seni Tari, 2025)
This study aims to describe the steps of Gobuk Dance packaging as teaching material through the Youtube application to display uploads containing Gobuk Dance in accordance with the Merdeka Curriculum, Phase E Learning Outcomes, namely: "Students are able to show and identify the meaning of creative dance according to the basic and supporting elements of dance works based on personal perspectives". The research location was carried out at the Yusda Arts Institute, Tanjung Tiram District, Batubara Regency in May-July 2024. A sample of 6 dancers. Data collection techniques were carried out by observation, interviews, documentation and validation tests. The research methodology uses ADDIE development. The results of the study explain the meaning of dance based on the main elements and supporting elements of the Gobuk Dance uploaded via the Youtube Application with a total duration of 16.00 minutes. This teaching material has passed the material feasibility test getting an average score of 4.7 and the media feasibility test getting an average score of 4.6 where from the score obtained this product is said to be worthy to be used as teaching material in learning activities for Senior High Schools.